2008
DOI: 10.1016/j.neuroimage.2007.10.055
|View full text |Cite
|
Sign up to set email alerts
|

Neural correlates of the processing of co-speech gestures

Abstract: In communicative situations, speech is often accompanied by gestures. For example, speakers tend to illustrate certain contents of speech by means of iconic gestures which are hand movements that bear a formal relationship to the contents of speech. The meaning of an iconic gesture is determined both by its form as well as the speech context in which it is performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

18
169
8
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 161 publications
(196 citation statements)
references
References 71 publications
(84 reference statements)
18
169
8
1
Order By: Relevance
“…The language network, together with inferior parietal cortex, is also engaged during sign language production (Emmorey et al, 2007;MacSweeney et al, 2008). Importantly, the first whole-brain pattern shows fronto-temporal areas that have repeatedly been found in studies of co-speech gesture perception, such as left inferior frontal gyrus and left superior temporal gyrus (Dick et al, 2012;Green et al, 2009;Holle et al, 2008Holle et al, , 2010Willems et al, 2007Willems et al, , 2009). In addition, these areas are associated with semantic processes, such as word retrieval (left inferior frontal gyrus: Amunts et al, 2004;de Zubicaray & McMahon, 2009;Thompson-Schill et al, 1999;Tremblay & Gracco, 2006; superior temporal gyrus: Graves et al, 2010;Heath et al, 2012;Khader et al, 2010).…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…The language network, together with inferior parietal cortex, is also engaged during sign language production (Emmorey et al, 2007;MacSweeney et al, 2008). Importantly, the first whole-brain pattern shows fronto-temporal areas that have repeatedly been found in studies of co-speech gesture perception, such as left inferior frontal gyrus and left superior temporal gyrus (Dick et al, 2012;Green et al, 2009;Holle et al, 2008Holle et al, , 2010Willems et al, 2007Willems et al, , 2009). In addition, these areas are associated with semantic processes, such as word retrieval (left inferior frontal gyrus: Amunts et al, 2004;de Zubicaray & McMahon, 2009;Thompson-Schill et al, 1999;Tremblay & Gracco, 2006; superior temporal gyrus: Graves et al, 2010;Heath et al, 2012;Khader et al, 2010).…”
Section: Discussionmentioning
confidence: 79%
“…It seems reasonable that cospeech gesture production engages the gesture network because it combines conceptual, as well as skill-related aspects of actions that are essential for the meaningful hand movements of co-speech gesturing. Importantly, the second activity pattern includes fronto-parietal areas that are also frequently found in neuroimaging studies of co-speech gesture perception (Dick et al, 2009;Holle et al, 2008;Kircher et al, 2009;Straube et al, 2011;Willems et al, 2007Willems et al, , 2009). …”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Or could the posterior superior temporal cortex possibly serve as a general audiovisual integration module (Beauchamp, Lee et al, 2004), which is capable both of lower form-level as well as higher semantic-conceptual integration processes? Unfortunately, the five published studies (Dick et al, in press;Green et al, in press;Holle et al, 2008;Willems et al, 2007Willems et al, , 2009 come to different conclusions: some studies argue that integration of iconic gestures and speech takes place in the IFG (Dick et al, in press;Willems et al, 2007Willems et al, , 2009, while others emphasize the involvement of posterior temporal areas (Green et al, in press;Holle et al, 2008). In some of these studies, alternative explanations unrelated to integration cannot be excluded.…”
Section: Introductionmentioning
confidence: 99%
“…In some of these studies, alternative explanations unrelated to integration cannot be excluded. One concern is that some studies could not demonstrate bimodal enhancement because they either lacked the necessary unimodal conditions (Dick et al, in press;Holle et al, 2008;Willems et al, 2007) or demonstrated bimodal enhancement only for a selected region of interest (Green et al, in press). …”
Section: Introductionmentioning
confidence: 99%